Pierre de L'Estoile and his world in the wars of religion, 1546-1611 - Hamilton, T (2014)
Pierre de L'Estoile (1546-1611) kept an extraordinary diary and collection in Paris during the Wars of Religion, recording everything from high-political scandals to low-life criminality during this crucial turning point in early modern history. The first extensive study of L'Estoile in any language, this thesis demonstrates how he negotiated and commemorated the conflicts that divided France as he engaged creatively with the rumours, ephemeral prints, poems, pictures, and books that he assembled in his diary and cabinet. It argues that the story of his life and times is the history of the civil wars in the making. While historians and literary scholars depend on L’Estoile’s diaries as an essential source of information, citing him as a mere passive observer, this thesis instead explores his subjectivity and interprets a wide range of hitherto unseen or neglected manuscript evidence that situates him in the Parisian society of royal office-holders and demonstrates his significance in the republic of letters. It follows a microhistorical approach to L'Estoile and his world in order to challenge established interpretations of his sources as evidence of a widespread mentality of eschatological anxiety in sixteenth-century France, instead focusing on L’Estoile’s personal responses to pieces in his collection. In this way, it critiques a common trend in cultural history to roam freely among ‘collective representations’ and argues for the importance of a precise analysis of social context, materiality, and individual subjectivity in reception studies.